Adaptability of F1 sunflower hybrids, created according to an integrated system of line selection for economically valuable traits in various agroclimatic zones - В. О. Бабич; І. Ю. Боровська; Я. Ю. Шарипіна; Я. Ф. Парій; Ю. В. Симоненко (Plant Varieties Studying and Protection, 2021)
Purpose. Determine the ecological plasticity and productivity of F1 sunflower hybrids created on the basis of maternal and parental lines, selected according to an accelerated selection system of lines resistant to herbicides (imidazoline and sulfonylurea groups) and broomrape (Orobanche cumana Wallr.).